Kedudukan Suami Istri dalam Kitab Tarjuman al-Mustafid Karya Abdul Rauf al Singkili - Gunawan Gunawan; John Supriyanto; Sulaiman M Nur (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This article examines Tarjuman Al-Mustafid’s interpretation of a phenomenal work by a scholar named Abdur Rauf As-Singkili Al-Fanshuri. This study focuses on the study of the concept of the role of husband and wife according to the Al-Qur’an based on the review of the tafsir Tarjuman Al-Mustafid book and the implementation of the role of husband and wife in daily life based on the concept of Al-Qur’an according to the book of tafsir Tarjuman Al-Mustafid. This research approach uses qualitative methods an the nature of the research is descriptive-analytical. The results of research on this issue are explaining the concept and implementation of the role of husband and wife in the Al-Quran study of the book of Tarjuman Al-Mustafid, Syekh Abdur Rauf said that men as leaders for women’s lives, husband and wife must try to realize a dream marriage, namely sakinah, mawaddah and warahmah because the presence of husband and wife can bring spiritual calm to their partners by way of muasyaroh bil ma’ruf in addressing the lack of a partner and coming to the wife in a good way because husband and wife are like clothes to cover each other’s shortcomings in order to maintain the marriage promise with the goal of hoping for the pleasure of Allah SWT.